Cosmopolitan Distribution of Endozoicomonas-Like Organisms and Other Intracellular Microcolonies of Bacteria Causing Infection in Marine Mollusks - Cano, Irene; Ryder, David; Webb, Steve C.; Jones, Brian J.; Brosnahan, Cara L.; Carrasco, Noelia; Bodinier, Barbara; Furones, Dolors; Pretto, Tobia; Carella, Francesca; Chollet, Bruno; Arzul, Isabelle; et al. (Frontiers in Microbiology, 2020)
Intracellular microcolonies of bacteria, in some cases developing large extracellular cysts, have been historically reported infecting a wide diversity of economically important mollusc species worldwide, sometimes associated with severe lesions and mass mortality events. As an effort to characterise those organisms, traditionally named as Rickettsia or Chlamydia -like organisms (RLO/CLO), via international collaboration, 98 samples comprising 20 mollusc species were collected over 10 countries and examined using histology and phylogenetic analysis. A 16S rRNA gene amplicon library-based sequencing showed the presence of different species of Endozoicomonas-like organisms (ELO) in all the mollusc species analysed, infecting primarily gill and digestive glands. Co-infections of ELOs with other intracellular bacteria were also observed. Subsequent phylogenetic analysis of Operational Taxonomic Units (OTU) revealed a novel microbial diversity associated with molluscan RLO/CLOs infection distributed along different taxa, including Spirochaetes phyla, Rickettsiales order, Simkaniaceae family, Mycoplasma and Francisella genera, and sulfur-oxidizing endosymbionts. Sequences like Francisella halioticida/philomiragia and Candidatus Brownia rhizoecola were also obtained. The presence of ELO sequences in the RLO/CLO infection was confirmed by standard PCR, Sanger sequencing, and by in situ hybridisation in a selection of samples. The phylogenetic analysis conducted in this study will allow for further characterization of the microbial community associated with Rickettsia and Chlamydia-like infection in marine molluscs and their correlation with severity of the lesions in order to reveal their role as endosymbionts, commensals or true pathogens.